Understanding dental hygienists’ knowledge, attitudes, and practices regarding HPV vaccination - Paula M. Cuccaro; Jihye Choi; Kawtar Zouaidi; Efrat K. Gabay; Michael Mackert; Josefine Ortiz Wolfe (Human Vaccines & Immunotherapeutics)
The American Dental Association and American Academy of Pediatric Dentistry encourage oral health professionals to strongly recommend human papillomavirus (HPV) vaccination to prevent HPV-associated oropharyngeal cancer. This study examined oral health professionals’ knowledge, attitudes, and practices regarding HPV vaccination. We used purposive sampling to recruit participants through state and national oral health societies and social media platforms. Flyers outlining eligibility criteria were distributed, and eligible participants completed an online survey. Primary measures included participants’ HPV-related knowledge, attitudes, and practices, and willingness to receive HPV-related training and recommend HPV vaccination to patients, including parents of adolescents. Only responses from dental hygienists (n = 380) were analyzed due to an insufficient sample size of dentists. Mostly female, White, and practicing in urban areas, hygienists had overall low awareness of the high prevalence of HPV and HPV vaccine efficacy in preventing several types of HPV-associated cancers. While the discussion of the HPV-oropharyngeal cancer link was perceived as relevant to their practice, participants generally disagreed with administering the vaccine in the dental office. Less than half of participants believed they were responsible for recommending the vaccine with low perceived knowledge and self-efficacy to discuss HPV vaccination with parents of adolescents. Despite the current lack of HPV vaccine recommendations in their practice, more than half of the participants were willing to educate their patients about the importance of the vaccine to prevent oropharyngeal cancer. HPV-focused educational interventions tailored to oral health practice may improve dental hygienists’ confidence and motivation to promote HPV vaccination for oral cancer prevention.